(untitled) (The Journal of Psychology and Sociology, 2018)
This article is devoted to an empirical study of the relationship between emotional burnout and personal characteristics of employees of the fire service of the Republic of Kazakhstan. The work of the employees of the firefighting service of the CoES of the Republic of Kazakhstan refers to the types of professional activity, the distinguishing feature of which is a constant confrontation with the danger. The methodological basis of the study was the three-component model of Maslach& Jackson. In modern scientific understanding, the specificity and uniqueness of the burnout syndrome is related to the symptoms of emotional exhaustion, depersonalization (cynicism) and reduction of personal achievements. Also, burnout includes a number of symptoms manifested in the cognitive and motivational spheres of the individual, in behavior and physical condition – common for these symptoms is their maladaptiveness. The purpose of the study was to study the relationship between emotional burnout and personal characteristics of employees of the fire service of the Republic of Kazakhstan. Methods of research – Maslach Burnout questionnaire, R. McCrae and P. Costa five-factor personal questionnaire and Tomsk G.V. Zalewskirigidity questionnaire (short TRQZ). The results of the study revealed a low level of emotional burnout in firefighters, the formation of individual burn-out phases. It is established that 43% of firefighters have a high level of reduction of professional achievements. The profile of the qualities necessary for fire department work is defined – adaptability, ability to work in a team, self-control, moderate rigidity. The results obtained can be used for professional selection and social and psychological support of personnel. Key words: personal characteristics of firefighters, emotional burnout, stressful impact, social and psychological support.